Experimental Study on the Relationship between the Natural Frequency and the Corrosion in Reinforced Concrete Beams - Liye Zhang; Limin Sun; Lijuan Dong (Advances in Materials Science and Engineering)
Due to many nondamage factors such as temperature, humidity, carbonation, and corrosion effects on natural frequency, the key problem of the application frequency-based method to detect damage is to reveal the rules of these factors affect natural frequency and further to eliminate their effects. The long-term characteristics of reinforced concrete structures require a lot of attention, especially in corrosive environment. In this paper, an experimental investigation was conducted to study the deflection and natural frequency of reinforced concrete beam in a marine environmental chamber for six corrosion stages (accelerated corrosion for 0, 20, 40, 70, 100, and 140 days). The experimental results demonstrated that deflection increases with corrosion time, while natural frequency decreases with corrosion time. Based on the accelerate corrosion test data of reinforced concrete beams, the general expression of the relationship between corrosion depth and natural frequency has been established through the fitting curve method. The polynomial model has been selected for establishing the relationship between steel corrosion depth (including the main reinforcement and stirrup) and natural frequency. The reason for selecting the polynomial model is that the sum of squares due to error (SSE) is closer to 0 and the coefficient of multiple determination (R-square) is closer to 1. This investigations help to discriminate the cause of reinforced concrete beams natural frequency change, to eliminate nondamage factors affects, and to apply many structural damage identification methods effectively.